China's Road and China's Dream An Analysis of the Chinese Political Decision-Making Process Through the National Party Congress - Hu, Angang (Springer Singapore, 2018)
This book defines China's road towards modernization with Chinese characteristics by systematically examining a typical Chinese political process - the National Congress of the Communist Party of China (CPC), during which diverse opinions are collected and a unified political consensus is formed. The author provides a detailed introduction to the background of and preparations for the 18th National Congress of CPC, as well as his personal experience of it as an attending representative. In addition, the book addresses a key problem, namely how China's leadership handover procedure gradually evolved into the current collective handover procedure, by analyzing its developmental history. The question of "how to implement China's leadership handover" is particularly meaningful, as it reflects the development of China's political system, and is also essential to the CPC flourishing and China's long-term prosperity. The author's personal experiences at the 18th National Congress made it possible to fully investigate the leadership handover procedure between Hu Jintao and Xi Jinping. Lastly, the book provides a detailed description of one highlight of the 18th CPC National Congress - the focus on ecological culture and green development - and discusses China's dream and its implications for history and the world.